A comparison of the returns of 'Regulation 28' compliant and non-compliant funds in South Africa - Noland, Stuart (Department of Finance and Tax, 2015)
The shift from defined benefit to defined contribution plans has exposed pensioners to a number of new risks which the South African government has been encouraged to mitigate through the aggressive implementation of retirement fund regulations. This study specifically focuses on the effect of asset allocation restrictions. The effect of these regulations is critically evaluated by comparing the long-term effects of both excess returns and risk-weighted returns of Regulation 28 compliant funds, to fully discretional non-compliant portfolios. With a population of 27 compliant funds and 21 non-compliant funds, it was found that while mean excess long-term return of non-compliant funds consistently outperforms compliant funds, there is no significant statistical difference between the two data sets. Additionally, while regulations successfully reduce the variation of excess returns of the compliant funds relative to the noncompliant funds, and the mean risk-weighted performance of compliant funds consistently outperformed non-compliant funds during the latter parts of the scoped period, no significant statistical difference was identified between compliant and non-compliant investment funds.